ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI STRUKTUR MODAL (PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE TAHUN 2010-2014) - Yudhiarti, Retno; Mahfud, M. Kholiq (Diponegoro Journal of Management, 2016)
This experiment aims to examine the factors that affect the capital structure at manufacturing companies. The dependent variable in this study is the capital structure as measured by DER. The independent variables are profitability, asset structure, sales growth, cash holdings, liquidity and size of the company. The manufacturing company which is the object of this research is manufacturing companies that went public and was listed on the Indonesia Stock Exchange. The sample population in this study is thirty companies listed on the Stock Exchange. The sampling technique used purposive sampling techniques to determine the sample, the study was conducted during the period 2010-2014, in order to obtain one hundred fifty research data. The data used in this research is secondary data drawn from the annual financial statements of companies listed on the Stock Exchange, which was then analyzed using multiple linear regression analysis which includes the classical assumption test and hypothesis testing using the coefficient of determination (R Â²), statistical test F, statistit t test with significance level of 5%. The results of this study indicate that company size has a positive and significant impact on the capital structure of companies manufacturing, sales growth has a positive effect but not significant to the company's capital structure manufacturing, asset structure and liquidity has a negative and significant impact on the capital structure of manufacturing companies, while profitability and cash holding has a negative effect and no significant effect on the capital structure of the manufacturing company.